2022
DOI: 10.1161/strokeaha.121.037297
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Management of Acute Stroke of Unknown Type in Resource-Limited Settings

Abstract: Stroke is the second leading cause of death and disability worldwide, with a disproportionate burden on low- and middle-income countries. Critical elements of guideline-based stroke care developed in high-income countries are not applicable to resource-limited settings, where lack of access to neuroimaging prevents clinicians from distinguishing between ischemic stroke and intracranial hemorrhage, requiring challenging clinical decision-making, particularly in the acute setting. We discuss strategies for acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 91 publications
1
9
0
1
Order By: Relevance
“…These conditions increase the susceptibilities of the patient for post-stroke aspiration pneumonia. Similar to other studies conducted in other countries, 18 , 52 this study also revealed that the risk of acquired aspiration pneumonia increases when the age of the patient increases.…”
Section: Discussionsupporting
confidence: 90%
“…These conditions increase the susceptibilities of the patient for post-stroke aspiration pneumonia. Similar to other studies conducted in other countries, 18 , 52 this study also revealed that the risk of acquired aspiration pneumonia increases when the age of the patient increases.…”
Section: Discussionsupporting
confidence: 90%
“…Current practice guidelines used in HICs, such as in our center, rely on the use of frequent video EEG monitoring, for example. Guidelines have been created for stroke in resource-limited settings; similar guidelines for IESS could be helpful for standardizing best practices in resource-limited settings [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Timely access to diagnostic services, particularly CT scans, is essential for successfully managing neurologic emergencies. The challenge of distinguishing between ischemic and hemorrhagic stroke, 8 the urgency to establish the need for time-sensitive neurosurgical interventions to address elevated intracranial pressure (ICP) such as external ventricular drainage (EVD) or decompressive craniectomy, and safety concerns surrounding lumbar punctures (LPs) 19 underscore the significance of CT scans. Of note, a standardized protocol for monitoring patients with TBI in resource-limited settings using clinical exams and CT scans was shown to be non-inferior to an ICP monitoring-guided approach.…”
Section: Increasing Access To Neuroimaging and Other Diagnosticsmentioning
confidence: 99%
“…Numerous vulnerabilities constrain the delivery of inpatient neurologic care throughout the world (►Fig. 1), including lack of trained personnel, 6,7 limited access to neuroimaging and other diagnostics, [8][9][10] limited availability of essential medicines and interventions, 6,11 insufficient physical space in inpatient facilities, 6,12,13 lack of inpatient rehabilitation services, 14 and underdevelopment of evidence-based guidelines for care delivery in resource-limited settings. 15 While high-income countries (HICs) have an average of 4.75 neurologists per 100,000 population, there are 0.03 neurologists per 100,000 population in low-income countries (LICs).…”
mentioning
confidence: 99%